Detection and Molecular Characterization of Bacillus cereus Isolated from Sago Processing Plants in Sarawak - Jasmin, Jaraee (Universiti Malaysia Sarawak(UNIMAS), 2018)
Sago processing industries are well-established and high potential industries in Sarawak. However, the contamination of bacteria might deteriorate its quality and become a concern to the public health. This study aimed to detect, quantify and characterize Bacillus cereus in sago processing in Sarawak, Malaysia. B. cereus was isolated from two selected sago processing mills in Sarawak. The prevalence and concentration of B. cereus in this study were determined firstly using selective agar and followed by using specific Polymerase Chain Reaction (PCR) by targeting specific virulence gene, haemolysin (hly) gene. A total of 120 samples consist of bark swab, sago pith, starch slurry, sago milk, sago flour and sago effluent were collected from each processing step in sago mills. It was revealed that B. cereus were present in 35% (42/120) of the samples. These isolates were subjected to molecular typing by using Enterobacterial Repetitive Intergenic Consensus Polymerase Chain Reaction (ERIC PCR) and Pulsed Field Gel Electrophoresis (PFGE). Both molecular typing method showed heterogeneity of the B. cereus strain. Susceptibility of all isolates towards 14 antibiotics was assessed using disk diffusion assay. B. cereus isolates were uniformly resistant to penicillin and ampicillin whereas B. cereus isolates were uniformly susceptible to imipenem and norfloxacin. Multiple antibiotic resistance (MAR) index were calculated based on the antibiotic resistance results. The MAR index for all isolates were also varies, ranged from 0.083 to 0.750. This study is useful in developing appropriate intervention strategies and establishing food safety standards in sago processing in Sarawak thus contribute in lowering the disease burden and assist in providing safer food to the society.